Effect of NaOH content on hydration, mineralogy, porosity and strength in alkali/sulfate-activated binders from ground granulated blast furnace slag and phosphogypsum. (June 2020) - Gijbels, Katrijn; Pontikes, Yiannis; Samyn, Pieter; Schreurs, Sonja; Schroeyers, Wouter
Abstract: This study investigates the effect of NaOH content on alkali/sulfate-activated binders from 90 wt% ground granulated blast furnace slag (GGBFS) and 10 wt% phosphogypsum (PG). Alkali activators were prepared with a NaOH molarity ranging from 0 M to 4 M. The hydration was monitored using in-situ X-ray diffraction (XRD) and isothermal calorimetry. The hydration product assemblage was investigated using XRD, thermogravimetric analysis (TGA), Fourier-transformed infrared (FTIR) spectroscopy, nitrogen adsorption/desorption and compressive strength tests. A molarity of 0 M NaOH gave rise to the highest porosity and highest strength, although setting occurred only after 7 days. From a molarity of 2 M NaOH and higher, ettringite disappeared and got replaced by a monosulfate phase (i.e., NaCa4 Al2 O6 (SO4 )1.5 .15H2 O) and amorphous aluminum-hydroxide. This study shows the potential of using GGBFS and PG for the development of novel by-product based cementitious binders. Highlights: The binder was a mixture of 90 wt% GGBFS and 10 wt% phosphogypsum. The NaOH molarity of the alkali activator ranged from 0 M to 4 M. A molarity of 0 M NaOH yielded highest porosity and strength, and slowest setting. Portlandite acted as a catalyst promoting further slag dissolution. From 2 M NaOH and higher, ettringite disappeared and carbonation was enhanced.